Failure to launch [videorecording (DVD)] - Dey, Tom; McConaughey, Matthew, 1969-; Parker, Sarah Jessica; Deschanel, Zooey, 1980- (Paramount Pictures, 2006)
Tripp is a thirtysomething slacker, but that doesn't mean that he is ready to give up the many benefits of living at home with his mom and dad. His desperate parents have had enough though, and after years of gentle nudging they soon realize that it is going to take a concerted effort to get Tripp out so they can enjoy their twilight years in peace. Realizing that their only hope for riding themselves of their reluctant-to-leave son, Al and Sue hope that on the off-chance Tripp will meet the woman of his dreams, the two enlist the help of a beautiful and talented woman in providing the romantic incentive needed to finally get their son out of the family home.